The Voice Bystander Effect: How Information Redundancy Inhibits Employee Voice - Hussain, Insiya; Shu, Rui; Tangirala, Subrahmaniam; Ekkirala, Srinivas (Academy of Management Journal, 2019)
Employees often remain silent rather than speak up to managers with work-related ideas, concerns, and opinions. As a result, managers can remain in the dark about issues that are otherwise well known to, or universally understood by, frontline employees. We propose a previously unexplored explanation for this phenomenon: Voice is prone to “bystander effects,” such that, the more certain information is shared among employees, the less any particular employee feels individually responsible for bringing up that information with managers. We theorize that such bystander effects are especially likely to occur when peers of focal employees, on average, enjoy high-quality relationships with managers and thereby have adequate relational access to voice up the hierarchy. Using a correlational study involving managers and employees working in teams in a Fortune 500 company, as well as two experimental studies (a laboratory study involving undergraduate students working in a hierarchical setting, and a scenario study with a sample of U.S.-based workers), we provide evidence for our conceptual model. We also discuss the theoretical and managerial implications of our findings.